SINERGITAS STAKEHOLDER DALAM PENGEMBANGAN EKONOMI LOKAL SEKTOR PERTANIAN AGROBISNIS (Studi Kasus Pada Komoditas Unggulan Jeruk Siam Gunuang Omeh) - Yani, Reza Fitri; SD, Zaili Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Local economic development depends on the government who can synergize with the various stakeholders involved for the realization of local economic development. There are quite a lot of stakeholders involved in the development of the local economy in the agricultural sector of agribusiness on the superior commodity of Siam Gunuang Omeh oranges but there are also many interests, interests and objectives of the involvement of each stakeholder in the utilization of the superior commodity of Gunuang Omeh oranges. This study aims to determine the synergy of stakeholders involved in local economic development through the agribusiness sector on the superior commodity of Siam Gunuang Omeh and to determine the inhibiting factors. This study used a qualitative method located in Gunuang Omeh District. The method used in determining the informants was the purposive sampling method, the research informants were the Food Crops, Horticulture and Plantation Office of Fifty Cities Regency, the Center for Agricultural Extension, Gunuang Omeh District, the Multi-Business Cooperative-Financial Institution for the Micro-Agribusiness of Siam Citrus Gunuang Omeh, Cv. T Jaya, traders / collectors and the community who live in the siam gunuang omeh environment by conducting interviews, observation and documentation so that the required data is obtained such as primary data and secondary data then which shows the results of the implementation of synergy between stakeholders and its inhibitors. The results of this study are the synergy of stakeholders in the development of the local economy in the agribusiness agricultural sector on the superior commodity of siam gunang omeh oranges that have been running but have not been maximized, this is due to several factors such as cooperation and weak coordination. Keywords: Stakeholder Synergy, Local Economic Development, Gunuang Omeh Siam Citrus